Embryonic Analytics' privacy statement - Osland, Asbjørn (London : SAGE Publications: SAGE Business Cases Originals, 2021)
A hypothetical start-up named Embryonic Analytics has to develop a privacy statement. The firm does contract preimplantation genetic diagnosis (PGD) for fertility firms to help couples avoid implanting embryos with recognized genetic defects. As a Direct to Consumer genetics testing firm, it also does genetic profiles for the man and woman whose semen and egg create the embryos. The results of the PGD process could highlight genetic disorders in either or both partners that were unknown before entering the in vitro fertilization process. The genetic profiles could uncover information that did not impact the embryos yet could be sensitive. Individuals have a right to medical confidentiality but a prospective partner might want to know of genetic threats to longevity or other important information.The management team has to determine whether to permit users to automatically opt-out of granting permission to use their information for research by pharmaceutical companies and also whether individuals would be offered the chance to participate in clinical trials. These two services could provide needed revenue streams to the firm. How concise and clear should the statement be versus comprehensive with all the legal protections desired by the lawyer? The genetic profiles offered to the man and woman have to be private and confidential yet students can wrestle with how much to divulge to a prospective spouse. Students can also decide whether the privacy statement is just legal protection for the firm or a way to display transparency to prospective clients or both.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Preimplantation genetic diagnosis -- Case studies; Medical records -- Access control -- Moral and ethical aspects -- Case studies